2022
DOI: 10.1186/s12915-022-01414-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of ROS-generating enzymes across the animal kingdom, with a focus on sponges (Porifera)

Abstract: Background Reactive derivatives of oxygen (reactive oxygen species; ROS) are essential in signalling networks of all aerobic life. Redox signalling, based on cascades of oxidation–reduction reactions, is an evolutionarily ancient mechanism that uses ROS to regulate an array of vital cellular processes. Hydrogen peroxide (H2O2) and superoxide anion (O2•−) are employed as signalling molecules that alter the oxidation state of atoms, inhibiting or activating gene activity. Here, we conduct metazoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…NO, and NOS control metamorphosis and symbiotic relationships in the desmosponge Amphimedon ( Ueda et al, 2016 ; Hewitt and Degnan, 2022 ). There is growing evidence that NO can modulate body contractions and coordinated behaviors in freshwater sponges Ephydatia muelleri ( Elliott and Leys, 2010 ), Spongilla lacustris ( Musser et al, 2021 ), and the marine sponge Tethya wilhelma ( Ellwanger and Nickel, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…NO, and NOS control metamorphosis and symbiotic relationships in the desmosponge Amphimedon ( Ueda et al, 2016 ; Hewitt and Degnan, 2022 ). There is growing evidence that NO can modulate body contractions and coordinated behaviors in freshwater sponges Ephydatia muelleri ( Elliott and Leys, 2010 ), Spongilla lacustris ( Musser et al, 2021 ), and the marine sponge Tethya wilhelma ( Ellwanger and Nickel, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…SOD1 and SOD2 are widely distributed across the metazoans, whereas SOD3 is absent in most sponges, a group of species which occupy a unique phylogenetic position as sister to other animal phyla. Traits unique to sponges have been logically traced back to the divergent evolution from a common ancestor [ 133 ]. A study of the ctenophore Mnemiopsis leidyi demonstrated substantial NOX gene loss with the retention of only NOX5 [ 133 , 134 ].…”
Section: Conservation and Evolution Of Ros Signalingmentioning
confidence: 99%
“…Traits unique to sponges have been logically traced back to the divergent evolution from a common ancestor [ 133 ]. A study of the ctenophore Mnemiopsis leidyi demonstrated substantial NOX gene loss with the retention of only NOX5 [ 133 , 134 ]. Ctenophores have been considered the earliest diverging animal lineage which share with bilaterians complex cell types such as neural cells [ 135 ].…”
Section: Conservation and Evolution Of Ros Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants can be either non-enzymatic (e.g., vitamins E, C, A, selenium, transferrin, and lactoferrin, ascorbic acid, glutathione, melatonin, carotenoids, flavonoids, proline), or specialised enzymes that vary in subcellular localisation, predominant substrate, and rate of reactivity 7,22,23 . The specialist enzymatic antioxidant families include those that target hydrogen peroxide (H 2 O 2 ), which is the major redox signalling ROS reviewed by 5,24,25 , and those that target superoxide anion radical (O 2•-) for the generation of H 2 O 2 as a product[reviewed by 26,27 .The three major families of antioxidants that target H 2 O 2 are monofunctional catalase (CAT), peroxiredoxin (PRX), and glutathione peroxidase (GPX) (Fig. 1A-C) 28,29,30,31 .…”
mentioning
confidence: 99%